Istem Kontrol Pemberian Pakan Ikan Lele Berbasis Internet of Things (IOT) Menggunakan Metode Fuzzy Sugeno - Frumentius Ngene Ngaji; Elta Sonalitha; Wahyu Dirgantara (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The development of technology in the field of fisheries is very rapid along with facilitating human work in the field. Human work can be done by tools such as feeding catfish in ponds automatically. This job is easy to do, but problems will arise when catfish are not fed at night or are fed too late, then the catfish will eat smaller catfish so that it can be detrimental to catfish farming owners. With this background, the author created a